Differential Expression of LncRNA MIAT and Its Clinical Significance in Intracranial Aneurysms - Fuquan Liu; Shuai Hao; Jingliyu Wang; Lei Chen; Ning Jiang; Laixing Liu; Xiangyi Wang (Brain and Behavior)
ABSTRACT Purpose: Intracranial aneurysm (IA) is characterized by localized dilation or ballooning of a blood vessel in the brain with life‐threatening consequences. This study set out to investigate the value of Long noncoding RNA myocardial infarction associated transcript (LncRNA MIAT) in diagnosis, rupture prediction, and prognosis for IA patients. Methods: The clinical characteristics of controls (100 cases) and IA patients, including 88 cases of ruptured IA (RIA) and 132 cases of unruptured IA (UIA), were analyzed using the chi‐square test and t‐test. MIAT expression in the serum was detected. The diagnostic efficacy of MIAT for IA was assessed through receiver operating characteristic (ROC) curve analysis. IA patients were categorized into low‐expression and high‐expression groups, and the correlation between MIAT expression and clinical indicators in IA patients was analyzed. The risk factors for IA rupture were analyzed. The correlation between MIAT expression and the overall survival of IA patients was assayed. The risk factors for poor prognosis in IA patients were analyzed. Results: LncRNA MIAT was elevated in IA patients, with higher expression in RIA patients than in UIA patients. MIAT expression could distinguish between healthy control and IA patients (area under the curve, AUC = 0.794, cut‐off value = 1.26, sensitivity = 68.64%, specificity = 83.00%, p < 0.001), healthy control and UIA patients (AUC = 0.782, cut‐off value = 1.15, sensitivity = 75.76%, specificity = 68.00%, p < 0.001), and UIA patients and RIA patients (AUC = 0.690, cut‐off value = 1.46, sensitivity = 76.14%, specificity = 68.94%, p < 0.001). MIAT expression was significantly associated with hypertension, IA location, and IA rupture status. MIAT was an independent risk factor for IA rupture. For every one‐unit increase in the relative expression of MIAT, the risk of poor prognosis in IA patients increased by 2.415 times (p = 0.014, 95% CI: 1.192–4.890). MIAT expression was correlated with the overall survival of IA patients and IA rupture in UIA patients. MIAT was an independent risk factor for poor prognosis of IA patients. For every one‐unit increase in the relative expression of MIAT, the risk of poor prognosis in IA patients increased by 2.415 times (p = 0.014, 95% CI: 1.192–4.890). Conclusion: Highly expressed MIAT is an independent risk factor for poor prognosis of IA and can support IA diagnosis and rupture prediction.